Acceptance of the Holders of Land Alienation Approval Towards the Premium Rate Payment Imposed by the State Authority - ABDULLAH, MUHAYMIN HAKIM (Journal of Social Transformation and Regional Development, 2020)
The legislation of land in Malaysia argues that any occupation of another person’s land without permission is unlawful, including on the government land. However, the state authorities have also alienating land to the people through the procedure of land application prescribed under?. Successful applicants will be charged payments of premium and other services. The payment claim is issued by the District Land Administrator through Form 5A Notice and is required to be cleared within a specific period of time according to the amount of the payment subjected to current land market value. for any payment failure, the alienation will be automatically revoked, thus re-application of land needs to be performed by the applicant if the land is still needed. According to preliminary data for a 5-year period from 2011 to 2015, a total of RM1,538,551,245.00 could not be collected by the Johor? state authority whereby a total of 1,100 notices issued have been revoked. This has affected the government’s revenue flow and its optimum use. For the general public, the impossible prospect of owning a land legally for residential purposes has caused concern. Therefore, the purpose of this study is to investigate the acceptance of the holders of land alienation approval towards the premium rates imposed by the state authority. A survey was conducted involving 229 respondents comprising the recipients of the alienation approval from various areas in the Johor Bahru district. The results of the study found 73% of respondents claimed that the premium payment fees charged were too high, while 26% of them claimed that the fees were high and only 1% said that the fees were moderate. None of the respondents stated that the premium was low. Therefore, an action must be taken by the authority to resolve this issue so that the holder who has received the ownership of the property can clear the premium payment in a timely manner. The purpose of this study is to identify the holders of the approval of the ownership of the premium payment rate imposed by the State Authority